A short letter and a long march: Michael Long and the Stolen Generations. - Gorman, Sean (Monash University Publishing, 2013)
A short letter and a long march: Michael Long and the Stolen Generations is part of the Telling Stories anthology. Telling Stories explores the interaction between literary culture and the public sphere in Australia. A short letter and a long march is a creative analysis of the genre of letters to the editor that are a specific feature of Australian newspapers by focusing on the letter Michael Long sent to the Age to protest against John Howard's denial of the Stolen Generations.